Demography and Localized Reservoirs of Diversity Underlie Global Divergence in the Giant Kelp Macrocystis pyrifera - E. C. Giles; A. Zaiko; H. G. Hampton; P. Saenz‐Agudelo; M. Scriver; D. Crossett; A. Sim; X. B. Zhang; T. Jedrecka; C. O. Blain; L. Rauhina‐August; C. E. Cornwall; et al. (Molecular Ecology, 2026)
Accurate assessments of genetic diversity are crucial for effective management of natural resources. Numerous evolutionary mechanisms and genetic constraints can shape lineage divergence, challenging our quantification of biodiversity. Here, using whole genome resequencing of globally distributed giant kelp, Macrocystis pyrifera (Order: Laminariales), we show clear separation of genetic groups across the Pacific based on 99 genotyped individuals and 799,160 SNPs. Additionally, divergence across 88 genotyped individuals (53 derived in silico and 35 newly sequenced) considering 5,466,408 SNPs is attributed to both historical demographic processes and differential selection. Between Central California and the South Pacific (Chile, Tasmania, New Zealand), high divergence has occurred with very weak levels of gene flow, with concurrent timing of divergence. In parts of the South Pacific, kelp exhibited nucleotide diversity comparable to Central Californian populations but showed stronger signals of directional selection and excesses of rare alleles, with fewer genes showing signs of negative selection and some carbon‐related genes under positive selection. In contrast, Central Californian kelp had an excess of genes with synonymous mutations and showed evidence of a recent population contraction, as indicated by linkage disequilibrium and Tajima's D . In all populations, genome‐wide background divergence was paired with narrow genomic intervals of high nucleotide diversity and high linkage disequilibrium, which predominantly contained pervasive repetitive sequences. These repetitive regions were larger and more often shared among genetic groups in the South Pacific. They also appear to harbour genes of unknown function and alleles at intermediate frequency, suggesting that giant kelp maintain reservoirs of diversity within linked repeats, and this phenomenon is more pronounced in South Pacific M. pyrifera . Overall, the discovery of differential selection and structural variation as key drivers of divergence points to underappreciated genomic mechanisms of adaptation in kelp. These results will be useful for informing efforts to enhance climate resilience by identifying the evolutionary potential underlying kelp forest adaptation in the future.

Structural characterisation of a fucose-rich acidic extracellular polysaccharide produced by Lindavia intermedia in New Zealand lakes - Cara A. Luiten; Ian M. Sims; Tracey J. Bell; Peter T. Northcote; A. Jonathan Singh; Andrew R. Lewis; Guilherme L. Sassaki; Phil M. Novis; Marc Schallenberg; Simon F.R. Hinkley (Algal Research, 2026)

Gut microplastics of two non-native freshwater fish species, Geophagus altifrons and Cichla orinocensis, in Singapore reservoirs - Xue Shen Teo; Kean Sim Lai; Jeffrey T. B. Kwik; Maxine A. D. Mowe; Darren C. J. Yeo (Aquatic Ecology, 2026)

First in situ observations of the goblin shark Mitsukurina owstoni - Aaron B. Judah; Alan J. Jamieson; Sarah R. D. Bingo; Megan E. Cundy; David A. Ebert; Steven Auscavitch; Harold K. Carlson; Tiffany Nicole G. Cunanan; Hayley B. Sims; Meagan Putts (Journal of Fish Biology, 2026)
We report the first live in situ observations of the iconic goblin shark ( Mitsukurina owstoni ) on a seamount near Jarvis Island in 2019 and on the slope of the Tonga Trench in 2024. Past observations are restricted to specimens hauled to the surface, resulting in limited knowledge of this species' ecology. These observations extend its known geographic and depth range considerably, and extend the depth range of lamniform sharks by 108 m. To further clarify habitat preferences and assess conservation status, further sampling, particularly with remote video, is required.

A targeted correction for arctic oscillation biases in seasonal forecasts - Ji-Han Sim; Baek-Min Kim; Ha-Rim Kim; Gaeun Kim; A-Young Lim; Yoo-Rim Jung; Ju Heon Kim; Geun Young Kim; Steven Cocke (Climate Dynamics, 2026)

Corn Starch/Soybean Wax Double Coated Biochar-based Controlled-release Nitrogen Fertilizer: Water Retention, Release Kinetics and Okra Growth - I. J. X. Yong; I. A. W. Tan; D. H. H. Sim; L. L. P. Lim (Water, Air, & Soil Pollution, 2026)

Diverse prokaryotic strategies associated with soil organic matter priming - M. Waibel; E. Paterson; T.E. Freitag; F. Abram; P.E. Hedley; J. Morris; L.J. Robinson; A. Sim; B. Thornton; F.P. Brennan (Applied Soil Ecology, 2026)

Exposure to traffic-related air pollution and the risk of premature rupture of membranes: a cohort analysis of the Korean CHildren’s ENvironmental health Study (Ko-CHENS) - Dong-Wook Lee; Kyung A. Lee; Jongmin Oh; Hwan-Cheol Kim; Sanghwan Song; Yun-Chul Hong; Eunhee Ha; Suejin Kim; Choonghee Park; Sanghwan Song; Jueun Lee; Huibyeol Park; et al. (Environmental Science and Pollution Research, 2026)

Characterisation of novel polysaccharide extracts from indigenous New Zealand ferns - Felicia Zhi Wen Peh; Kelvin K.T. Goh; Cara A. Luiten; Ian M. Sims; Lara Matia-Merino (Food Hydrocolloids, 2026)

Inhibition of Microcystis aeruginosa Kützing by seven submerged macrophytes and the influence of season and decomposing plant leachate - Huy A. Luong; Ann-Marie Rohlfs; Jordan A. Facey; Anne Colville; Darren Z. H. Sim; Simon M. Mitrovic (Hydrobiologia, 2026)

Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

Isolation and characterisation of cell wall polysaccharides from taewa (Māori potatoes; Solanum tuberosum L.) - Cara.A. Luiten; Simon F.R. Hinkley; Nick R. Roskruge; Saii A. Semese; Anne-Louise M. Heath; Tracy L. Perry; Nancy J. Rehrer; Ian M. Sims (Food Hydrocolloids, 2026)

Pan‐Arctic Peatlands Have Expanded During Recent Warming - J. Handley; R. E. Fewster; T. G. Sim; S. Hodson; B. Parker; K. Crichton; D. Charman; K. Anderson; M. Garneau; M. Väliranta; D. W. Beilman; G. T. Swindles; et al. (Global Change Biology, 2026)
The fate of carbon stored in Arctic peatlands remains uncertain because of the complex nature of the effects of climate change on permafrost and peatland carbon cycling. Expansion and/or shrinkage of Arctic peatlands under climate change also remain unknown due to lack of ground data and difficulties detecting changes in the extent of these ecosystems, meaning that land surface model predictions currently inadequately quantify Arctic terrestrial carbon storage changes. Pan‐Arctic shifts in peatland extent would profoundly change the fate of carbon in the terrestrial Arctic. Here, we tackle this knowledge gap by answering three main questions: (a) has lateral expansion occurred in Arctic peatlands as a response to recent warming? (b) if so, how fast has this occurred? (c) how does the response vary regionally? To answer these, we collected a dataset (12 peatland sites, 91 peat cores) combining peat cores collected across two latitudinal (north–south) transects: one in the European Arctic and one in the Canadian Arctic. In each region, we selected three peatland sites, with cores collected from transects spanning the peat‐edge to the peat‐centre. Our large‐scale dataset shows that peatlands have expanded, often rapidly, with some rates exceeding ~1 m per year since 1950 AD. This rapid expansion has occurred during a period of widespread Arctic warming and is still ongoing: two thirds (8/12) of our peatland sites evidence new peat formation after ~1990 AD based on age‐depth models constrained by 14 C and 210 Pb dating. Given that our sites comprise a broad range of Arctic conditions, we expect peatland expansion to be a pan‐Arctic phenomenon. Within specific regions, there are constraints on peat expansion including topographical limits, but we present the basis for future work to estimate pan‐Arctic peatland expansion, plus the associated carbon cycle implications under future climate change.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Revision of Odontella litigiosa (Bacillariophyta): life-cycle and taxonomy - David M. Williams; Pat A. Sims; Edgley César; Jakub Witkowski (Systematics and Biodiversity, 2025)

Associations of pre- and postnatal levels of three heavy metals with visual impairment in 3-year-old children - Dajeong Ham; Sung Yeon Kim; Sanghyuk Bae; Suejin Kim; Choonghee Park; Sanghwan Song; Jueun Lee; Huibyeol Park; JungHeum Jo; A-Ra Jung; Seung Do Yu; Hyun Jeong Kim; et al. (Environmental Research, 2025)

Persistent Genomic Erosion in Whooping Cranes Despite Demographic Recovery - Claudia Fontsere; Samuel A. Speak; Andrew J. Caven; Juan Antonio Rodríguez; Xuejing Wang; Carolina Pacheco; Molly Cassatt‐Johnstone; Georgette Femerling; Brigid Maloney; Jennifer Balacco; Joanna Collins; Ying Sims; et al. (Molecular Ecology, 2025)
Integrating in‐situ (wild) and ex‐situ (captive) conservation efforts can mitigate genetic diversity loss and help prevent extinction of endangered wild populations. The whooping crane ( Grus americana ) experienced severe population declines in the 18th century, culminating in a collapse to ~20 individuals by 1944. Legal protections and conservation actions have since increased the census population from a stock of 16 individuals to approximately 840 individuals, yet the impact on genomic diversity remains unclear. We analysed the temporal dynamics of genomic erosion by sequencing a high‐quality reference genome, and re‐sequencing 16 historical (years 1867–1893) and 37 modern (2007–2020) genomes, including wild individuals and four generations of captive‐bred individuals. Genomic demographic reconstructions reveal a steady decline, accelerating over the past 300 years with the European settlement of North America. Temporal genomic analyses show that despite demographic recovery, the species has lost 70% of its historical genetic diversity and has increased its inbreeding. Although the modern population bottleneck reduced the ancestral genetic load, modern populations possess more realised load than masked load, possibly resulting in a chronic loss of fitness. Integrating pedigree and genomic data, we underscore the role of breeding management in reducing recent inbreeding. Yet ongoing heterozygosity loss, load accumulation, and persistent effects of historical inbreeding (i.e., background inbreeding) argue against the species' downlisting from its current Endangered status on the IUCN Red List and the Endangered Species Act. The presence of private genetic variation in wild and captive populations suggests that wild‐captive crosses could enhance genetic diversity and reduce the realised load. Our findings emphasise the role of genomics in informing conservation management and policy.

Strategically timing land protection decisions to enhance biodiversity benefits - Paul R. Armsworth; Rachel E. Fovargue; Amanda A. Hyman; Gwenllian D. Iacona; Charles B. Sims; Hyun Seok Yoon (Conservation Biology, 2025)
Choices conservation organizations make when designing and implementing protected area strategies affect the timing of land protection. Well‐timed habitat protection will have a greater impact on biodiversity outcomes; yet, decisions affecting the timing of protection have received much less attention than other aspects of protected area design. We reviewed evidence on the timing of protected area establishment and on temporal variation in factors influencing the ecological effectiveness and cost‐effectiveness of establishing protected areas. Protected area coverage often increases in episodic bursts rather than at some uniform rate. Moreover, temporal variation in biodiversity indicators, habitat conversion threats, and the cost of protecting land suggests that the conservation benefit of protecting land at some times will be greater than that at others. Conservation organizations increase their flexibility to choose when they protect land by using flexibility‐creating mechanisms, such as loans, multiyear budgeting, and endowment management. Models and theory suggest how this can be done to have the largest positive impact for conservation by exploiting long‐ and short‐term variation in factors that affect the rate of biodiversity return on protected area investments.

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Atherosclerotic Cardiovascular Disease in Gulf War Veterans in Relation to Deployment Exposures - Sarah T. Ahmed; Ruosha Li; Lea Steele; Peter Richardson; Kellie Sims; Rachel Quaden; Kelly M. Harrington; Vijay Nambi; John M. Gaziano; Robert Morgan; George L. Delclos; Drew A. Helmer (Cardiovascular Toxicology, 2025)
Many 1990–1991 Gulf War Veterans (GWVs) were exposed to toxicants and environmental hazards during deployment, including oil well fire smoke, chemical/biological agents, pyridostigmine bromide (PB) pills, and pesticides. Multiple constituents of smoke are associated with increased risk for atherosclerotic cardiovascular diseases (ASCVD), and other toxic exposures have been associated with autonomic and lipid dysfunction. We used data from the Gulf War Era Cohort and Biorepository Study of veterans deployed to Gulf War in 1990–1991 ( n = 942). We evaluated the association of deployment exposures (no, yes (1–6 days), (7–30 days), (31 + days), and not sure) with clinical risk factors (hypertension, diabetes, high cholesterol) and ASCVD using multivariable logistic regression. We adjusted for all clinical risk factors in the models to test the association of military exposures and ASCVD. We found that 7–30 days exposure to oil well fire smoke (OR: 2.95, CI: 1.40, 6.19), PB pills (OR: 2.37, CI: 1.06, 5.32), and chemical/biological agents (OR: 3.60, CI: 1.04, 12.51) were associated with ASCVD. Exposure to chemical/biological agents for 7–30 days was also associated with hypertension (OR: 4.18, CI: 1.48, 11.86) and for 31 + days was associated with ASCVD (OR: 4.24, CI:1.20, 14.94). The associations between oil well fire smoke and chemical/biological agents with ASCVD remained significant in models adjusting for clinical risk factors. For GWVs, exposure to oil well fire smoke, chemical/biological agents, and PB pills were associated with ASCVD. These exposures may represent population-specific risk enhancers for ASCVD and may be considered in individualized clinical risk assessment.

Genomic infrastructure for cetacean research and conservation: reference genomes for eight families spanning the cetacean tree of life - Phillip A. Morin; Bernhard Bein; Chiara Bortoluzzi; Yury V. Bukhman; Taylor Hains; Dorothea Heimeier; Marcela Uliano-Silva; Dominic E. Absolon; Linelle Abueg; Jessica Antosiewicz-Bourget; Jennifer R. Balacco; Robert K. Bonde; et al. (Frontiers in Marine Science, 2025)
Reference genomes from representative species across families provide the critical infrastructure for research and conservation. The Cetacean Genomes Project (CGP) began in early 2020 to facilitate the generation of near error-free, chromosome-resolved reference genomes for all cetacean species. Towards that goal, and using the methods, goals and genome assembly quality standards of the Vertebrate Genomes Project (VGP), we generated 13 new reference genomes across eight of the 14 cetacean families. Additionally, we summarize the genome assembly characteristics for 18 species, including these newly-generated and five published genome assemblies that meet the completeness and quality standards. We infer ancestral linkage groups (ALG) for cetaceans, showing that the ancestral karyotype of 22 ALGs is largely conserved in extant species, except for Ziphiidae, and for Balaenidae and Kogiidae, which exhibit similar independent fusions. Gene annotation, characterization of historical demography, heterozygosity and runs of homozygosity (ROH) reveal important information for conservation applications. By comparing the new reference genomes to previous draft assemblies, we show that the reference genomes have enhanced characteristics that will support and promote scientific research. Specifically, the genomes improve resolution and characterization of repetitive elements, provide validation (or exclusion) of genes linked to complex traits, and allow more complete characterization of gene regions such as the highly complex Major Histocompatibility Complex (MHC) Class I and II gene clusters that are important for population health.

Excessive Gestational Weight Gain, Independent of Body Mass Index, Is Associated With Child Fat Mass Index at Age 2 Years in the Growing life, Optimizing Wellness Study - Margaret Ballard; Jessica L. Saben; Rebecca A. Krukowski; Elisabet Børsheim; Clark R. Sims; Hallie Samuel; Lisa Jansen; Aline Andres (Journal of the Academy of Nutrition and Dietetics, 2025)

Per- and polyfluoroalkyl substances (PFAS) in the rivers of the Western United States - D. B. Sims; J. R. Monk; D. Woldetsadik; A. C. Hudson; M. C. Garner; K. Lindley; J. Piacentini; A. C. Buch; C. Cohu; C. S. Duvall; J. Blaszczak; J. Krause; et al. (International Journal of Environmental Science and Technology, 2025)

A Novel Approach to Estimate Natural Attenuation of Solutes Beneath a Century-Old Waste Rock Dump: Implications for Future Waste Rock Disposal Facility Groundwater Quality Impacts - Andy Davis; N. Sims; J. Collord; A. Chouinard (Mine Water and the Environment, 2025)

Automated abdominal aortic calcification scoring from vertebral fracture assessment images and fall-associated hospitalisations: the Manitoba Bone Mineral Density Registry - Marc Sim; Abadi K. Gebre; Jack Dalla Via; Siobhan Reid; Mohammad Jafari Jozani; Douglas Kimelman; Barret A. Monchka; Syed Zulqarnain Gilani; Zaid Ilyas; Cassandra Smith; David Suter; John T. Schousboe; et al. (GeroScience, 2025)
Abdominal aortic calcification (AAC), a subclinical measure of cardiovascular disease (CVD) that can be assessed on vertebral fracture assessment (VFA) images during osteoporosis screening, is reported to be a falls risk factor. A limitation to incorporating AAC clinically is that its scoring requires trained experts and is time-consuming. We examined if our machine learning (ML) algorithm for AAC (ML-AAC24) is associated with a higher fall-associated hospitalisation risk in the Manitoba Bone Mineral Density (BMD) Registry. A total of 8565 individuals (94.0% female, age 75.7 ± 6.8 years) who had a BMD and VFA image from DXA between February 2010 and December 2017 were included. ML-AAC24 was categorised based on established categories (ML-AAC24 = low < 2; moderate 2 to < 6; high ≥ 6). Cox proportional hazards models assessed the relationship between ML-AAC24 categories and incident fall-associated hospitalisations obtained from linked health records (mean ± SD follow-up, 3.9 ± 2.2 years). Individuals with moderate (9.6%) and high ML-AAC24 (11.7%) had a greater proportion of fall-associated hospitalisations, compared to those with low ML-AAC24 (6.0%). In age and sex-adjusted models, compared to low ML-AAC24, moderate (HR 1.49, 95% CI 1.24–1.79) and high ML-AAC24 (HR 1.89, 95% CI 1.56–2.28) were associated with greater hazards for a fall-associated hospitalisation. Results were comparable (HR 1.37, 95% CI 1.13–1.65 and HR 1.60, 95% CI 1.31–1.95, respectively) after multivariable adjustment, including prior falls and CVD, as well as medication use. Integrating ML-AAC24 into bone density machine software to identify high risk individuals would opportunistically provide important information on fall and cardiovascular disease risk to clinicians for evaluation and intervention.

Anomalous temperatures increase occupational injuries, illnesses and associated cost burden in Australia - Matthew A. Borg; Jianjun Xiang; Olga Anikeeva; Bertram Ostendorf; Blesson Varghese; Keith Dear; Dino Pisaniello; Alana Hansen; Kerstin Zander; Malcolm R. Sim; Peng Bi (Urban Climate, 2025)

Prospective life cycle assessment of climate and biodiversity impacts of meat‐based and plant‐forward meals: A case study of Indonesian and German meal options - Sandra G. Marquardt; P. James Joyce; Giles Rigarlsford; Mariska Dötsch‐Klerk; Kathelijn van Elk; Jonathan Doelman; Vassilis Daioglou; Mark A. J. Huijbregts; Sarah Sim (Journal of Industrial Ecology, 2024)
The emerging field of prospective life cycle assessment (pLCA) offers opportunities for evaluating the environmental impacts of possible future consumption shifts. One such shift involves a transition from meat‐based to plant‐forward diets, acknowledged to mitigate environmental impacts of the food system under present day conditions. Current diets are often meat intensive (“meat‐based”), whilst “plant‐forward” diets include mainly plant‐based foods, encompassing flexitarian, vegetarian, and vegan diets. Here we illustrate the application of pLCA in a case study of meal options, implementing shared socio‐economic pathway scenarios in the LCA background system to represent future production conditions. We assess the climate footprints and land‐based biodiversity footprints of a typical meat‐based meal in Germany and Indonesia compared to a plant‐forward meal in both countries (i.e., four meals), now and in 2050. Our findings show that the plant‐forward alternative maintains a lower impact per serving in all future scenarios. At the same time, the reduction in impact for the meat‐based meals is more pronounced in future scenarios due to shifts in the agricultural system. Our findings highlight the importance of supply‐side measures to produce lower‐impact ingredients, complementing demand‐side interventions to reshape food consumption. Results are further evaluated in cultural and nutritional contexts, highlighting the practical decision‐making constraints faced by consumers. We find potential “leakage” effects in calories and nutrition when choosing a lower‐impact, plant‐forward meal. These leakage effects should be considered in future studies seeking to evaluate the environmental implications of meal substitutions in the context of broader dietary requirements.

Optimizing the detection of N-nitrosamine mutagenicity in the Ames test - Robert H. Heflich; Michelle E. Bishop; Roberta A. Mittelstaedt; Jian Yan; Sharon K. Guerrero; Audrey M. Sims; Kamela Mitchell; Nyosha Moore; Xilin Li; Nan Mei; Rosalie K. Elespuru; Sruthi T. King; et al. (Regulatory Toxicology and Pharmacology, 2024)

A framework for optimising opportunistic collaborative syntheses to propel ecological conservation - Ana M.M. Sequeira; Amanda E. Bates; Graeme Hays; David W. Sims; Samantha Andrzejaczek; Asta Audzijonyte; Julia K. Baum; Martin Beal; Barbara Block; Joshua Cinner; Kaitlyn Cowley; Eric Gilman; et al. (Biological Conservation, 2024)

Nanoneedles like FeP engineered on Ni-Foam as an effective catalyst towards overall alkaline freshwater, urea, and seawater splitting - Anjali Gupta; Cassia A. Allison; Rishabh Srivastava; Anuj Kumar; Mina Sim; Jeffery Horinek; Wang Lin; Felipe M. de Souza; Sanjay R. Mishra; Felio Perez; Ram K. Gupta; Tim Dawsey (Fuel, 2024)

Occurrence, source, and ecological risk of pharmaceuticals and illicit drugs in surface water in Las Vegas, USA - D. B. Sims; J. R. Monk; M. C. Garner; A. C. Hudson; J. E. Keller; C. Aguaiza; K. Lindley; D. Woldetsadik; A. C. Buch (International Journal of Environmental Science and Technology, 2024)

Global habitat predictions to inform spatiotemporal fisheries management: Initial steps within the framework - Heather D. Bowlby; Jean-Noël Druon; Jon Lopez; Maria José Juan-Jordá; María Teresa Carreón-Zapiain; Frederic Vandeperre; Agostino Leone; Brittany Finucci; Philippe S. Sabarros; Barbara A. Block; Haritz Arrizabalaga; Pedro Afonso; et al. (Marine Policy, 2024)

Fractionation and characterisation of pectin-rich extracts from garlic biomass - Piyachat Sunanta; Sarana Rose Sommano; Cara A. Luiten; Mahdieh Ghofrani; Ian M. Sims; Tracey J. Bell; Susan M. Carnachan; Simon F.R. Hinkley; Vassilis Kontogiorgos (Food Chemistry, 2024)

Ecological Validation and Practical Challenges of Conducting Dietary Analysis in Athletic Individuals Using a Novel Remote Food Photography Method Mobile Phone Application - Charlie J. Roberts; Nicholas D. Gill; Brett A. Baxter; Stacy T. Sims (Journal of Science in Sport and Exercise, 2024)
Purpose Dietary analysis is an important part of the sports nutrition practitioners’ role, however the ability to accurately collect and analyze dietary intake data is questionable. The remote food photography method (RFPM) has been proposed as a low-burden and potentially valid approach to collecting and interpreting dietary intake data. Preliminary research suggests that this is valid in some athletic populations, however the ecological validation in real-life settings warrants further investigation. Methods Twenty athletic individuals completed simultaneous three-day RFPM diaries and weighed food diaries for the analysis of energy, protein, carbohydrate, and fat. Participants were required to provide details alongside provided photographs that did not include food weights to allow for the estimation of nutrient intake from minimally invasive photographs and descriptions. Results RFPM demonstrated non-significant random and systematic error against the weighed food diary for energy, protein, carbohydrate, and fat at − 20.0 ± 455.5 kcal, − 2.9 ± 34.6 g, − 12.4 ± 49.3 g and 2.3 ± 26.8 g, respectively. Coefficient of variation suggest acceptable agreement between RFPM and weighed food diary for energy and poor agreement for protein, carbohydrate, and fat. Considerable variability is observed in the individual calculated values, with the least and greatest difference being 0% and − 83.0%, respectively. Conclusion The results indicate that the RFPM may be an ecologically valid tool for the collection and analysis of dietary intake data on a group level; on an individual basis, data and subsequent recommendations based on this method must be applied with caution.

Context-dependent changes in maritime traffic activity during the first year of the COVID-19 pandemic - Alexandra Loveridge; Christopher D. Elvidge; David A. Kroodsma; Timothy D. White; Karen Evans; Akiko Kato; Yan Ropert-Coudert; Julia Sommerfeld; Akinori Takahashi; Robert Patchett; Benjamin Robira; Christian Rutz; et al. (Global Environmental Change, 2024)

The dynamic influence of subsurface geological processes on the assembly and diversification of thermophilic microbial communities in continental hydrothermal systems - Kenneth W.W. Sims; Cole M. Messa; Sean R. Scott; Andrew D. Parsekian; Andrew Miller; Abraham L. Role; Timothy P. Moloney; Everett L. Shock; Jacob B. Lowenstern; R. Blaine McCleskey; Matthew A. Charette; Bradley J. Carr; et al. (Geochimica et Cosmochimica Acta, 2023)

Pea aphid odorant-binding protein ApisOBP6 discriminates between aphid sex pheromone components, aphid alarm pheromone and a host plant volatile - Cassie Sims; Michael A. Birkett; Neil J. Oldham; Robert A. Stockman; David M. Withall (Insect Biochemistry and Molecular Biology, 2023)

Current and projected heatwave-attributable occupational injuries, illnesses, and associated economic burden in Australia - Matthew A. Borg; Jianjun Xiang; Olga Anikeeva; Bertram Ostendorf; Blesson Varghese; Keith Dear; Dino Pisaniello; Alana Hansen; Kerstin Zander; Malcolm R. Sim; Peng Bi (Environmental Research, 2023)

Land use diversification may mitigate on‐site land use impacts on mammal populations and assemblages - Koen J. J. Kuipers; Sarah Sim; Jelle P. Hilbers; Stefanie K. van den Berg; Melinda M. J. de Jonge; Krista Trendafilova; Mark A. J. Huijbregts; Aafke M. Schipper (Global Change Biology, 2023)
Land use is a major cause of biodiversity decline worldwide. Agricultural and forestry diversification measures, such as the inclusion of natural elements or diversified crop types, may reduce impacts on biodiversity. However, the extent to which such measures may compensate for the negative impacts of land use remains unknown. To fill that gap, we synthesised data from 99 studies that recorded mammal populations or assemblages in natural reference sites and in cropland and forest plantations, with or without diversification measures. We quantified the responses to diversification measures based on individual species abundance, species richness and assemblage intactness as quantified by the mean species abundance indicator. In cropland with natural elements, mammal species abundance and richness were, on average, similar to natural conditions, while in cropland without natural elements they were reduced by 28% and 34%, respectively. We found that mammal species richness was comparable between diversified forest plantations and natural reference sites, and 32% lower in plantations without natural elements. In both cropland and plantations, assemblage intactness was reduced compared with natural reference conditions, but the reduction was smaller if diversification measures were in place. In addition, we found that responses to land use were modified by species traits and environmental context. While habitat specialist populations were reduced in cropland without diversification and in forest plantations, habitat generalists benefited. Furthermore, assemblages were impacted more by land use in tropical regions and landscapes containing a larger share of (semi)natural habitat compared with temperate regions and more converted landscapes. Given that mammal assemblage intactness is reduced also when diversification measures are in place, special attention should be directed to species that suffer from land use impacts. That said, our results suggest potential for reconciling land use and mammal conservation, provided that the diversification measures do not compromise yield.

Grass variety selection of microbial community composition is associated with differences in soil CO2 emissions - M.E. Giles; S. Caul; D. King; S. Mitchell; A. Sim; R. Neilson; E. Paterson (Applied Soil Ecology, 2023)

Determinants of Gestational Weight Gain and Its Impact on Offspring Adiposity at Age 2 Years - M. Ballard; A. Andres; K. Shankar; R. Krukowski; E. Børsheim; C. Sims (Journal of the Academy of Nutrition and Dietetics, 2023)

Coral assemblages at higher latitudes favor short‐term potential over long‐term performance - James Cant; James D. Reimer; Brigitte Sommer; Katie M. Cook; Sun W. Kim; Carrie A. Sims; Takuma Mezaki; Cliodhna O'Flaherty; Maxime Brooks; Hamish A. Malcolm; John M. Pandolfi; Roberto Salguero‐Gómez; et al. (Ecology, 2023)
The persistent exposure of coral assemblages to more variable abiotic regimes is assumed to augment their resilience to future climatic variability. Yet, while the determinants of coral population resilience across species remain unknown, we are unable to predict the winners and losers across reef ecosystems exposed to increasingly variable conditions. Using annual surveys of 3171 coral individuals across Australia and Japan (2016–2019), we explore spatial variation across the short‐ and long‐term dynamics of competitive, stress‐tolerant, and weedy assemblages to evaluate how abiotic variability mediates the structural composition of coral assemblages. We illustrate how, by promoting short‐term potential over long‐term performance, coral assemblages can reduce their vulnerability to stochastic environments. However, compared to stress‐tolerant, and weedy assemblages, competitive coral taxa display a reduced capacity for elevating their short‐term potential. Accordingly, future climatic shifts threaten the structural complexity of coral assemblages in variable environments, emulating the degradation expected across global tropical reefs.

High interannual surface p CO 2 variability in the southern Canadian Arctic Archipelago's Kitikmeot Sea - Richard P. Sims; Mohamed M. M. Ahmed; Brian J. Butterworth; Patrick J. Duke; Stephen F. Gonski; Samantha F. Jones; Kristina A. Brown; Christopher J. Mundy; William J. Williams; Brent G. T. Else (Ocean Science, 2023)
Warming of the Arctic due to climate change means the Arctic Ocean is now free from ice for longer, as sea ice melts earlier and refreezes later. Yet, it remains unclear how this extended ice-free period will impact carbon dioxide (CO2) fluxes due to scarcity of surface ocean CO2 measurements. Baseline measurements are urgently needed to understand spatial and temporal air–sea CO2 flux variability in the changing Arctic Ocean. There is also uncertainty as to whether the previous basin-wide surveys are representative of the many smaller bays and inlets that make up the Canadian Arctic Archipelago (CAA). By using a research vessel that is based in the remote Inuit community of Ikaluqtuutiak (Cambridge Bay, Nunavut), we have been able to reliably survey pCO2 shortly after ice melt and access previously unsampled bays and inlets in the nearby region. Here we present 4 years of consecutive summertime pCO2 measurements collected in the Kitikmeot Sea in the southern CAA. Overall, we found that this region is a sink for atmospheric CO2 in August (average of all calculated fluxes over the four cruises was −4.64 mmol m−2 d−1), but the magnitude of this sink varies substantially between years and locations (average calculated fluxes of +3.58, −2.96, −16.79 and −0.57 mmol m−2 d−1 during the 2016, 2017, 2018 and 2019 cruises, respectively). Surface ocean pCO2 varied by up to 156 µatm between years, highlighting the importance of repeat observations in this region, as this high interannual variability would not have been captured by sparse and infrequent measurements. We find that the surface ocean pCO2 value at the time of ice melt is extremely important in constraining the magnitude of the air–sea CO2 flux throughout the ice-free season. However, further constraining the air–sea CO2 flux in the Kitikmeot Sea will require a better understanding of how pCO2 changes outside of the summer season. Surface ocean pCO2 measurements made in small bays and inlets of the Kitikmeot Sea were ∼ 20–40 µatm lower than in the main channels. Surface ocean pCO2 measurements made close in time to ice breakup (i.e. within 2 weeks) were ∼ 50 µatm lower than measurements made > 4 weeks after breakup. As previous basin-wide surveys of the CAA have focused on the deep shipping channels and rarely measure close to the ice breakup date, we hypothesize that there may be an observational bias in previous studies, leading to an underestimate of the CO2 sink in the CAA. These high-resolution measurements constitute an important new baseline for gaining a better understanding of the role this region plays in the uptake of atmospheric CO2.

Revisiting the mutagenicity and genotoxicity of N-nitroso propranolol in bacterial and human in vitro assays - Xilin Li; Yuan Le; Ji-Eun Seo; Xiaoqing Guo; Yuxi Li; Si Chen; Roberta A. Mittelstaedt; Nyosha Moore; Sharon Guerrero; Audrey Sims; Sruthi T. King; Aisar H. Atrakchi; et al. (Regulatory Toxicology and Pharmacology, 2023)

Agmatine-IRF2BP2 interaction induces M2 phenotype of microglia by increasing IRF2-KLF4 signaling - Jiwon Kim; A Young Sim; Sumit Barua; Jong Youl Kim; Jong Eun Lee (Inflammation Research, 2023)

DNA damage-induced stalling of transcription drives aging through gene expression imbalance - Austin A. Sims; Aditi U. Gurkar (DNA Repair, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Impact of land cover, rainfall and topography on flood risk in West Java - Rahmawati Rahayu; Simon A. Mathias; Sim Reaney; Gianni Vesuviano; Rusmawan Suwarman; Agus M. Ramdhan (Natural Hazards, 2023)
Flooding represents around 32% of total disasters in Indonesia and disproportionately affects the poorest of communities. The objective of this study was to determine significant statistical differences, in terms of river catchment characteristics, between regions in West Java that reported suffering from flood disasters and those that did not. Catchment characteristics considered included various statistical measures of topography, land-use, soil-type, meteorology and river flow rates. West Java comprises 154 level 9 HydroSHEDS sub-basin regions. We split these regions into those where flood disasters were reported and those where they were not, for the period of 2009 to 2013. Rainfall statistics were derived using the CHIRPS gridded precipitation data package. Statistical estimates of river flow rates, applicable to ungauged catchments, were derived from regionalisation relationships obtained by stepwise linear regression with river flow data from 70 West Javanese gauging stations. We used Kolmogorov–Smirnov tests to identify catchment characteristics that exhibit significant statistical differences between the two sets of regions. Median annual maximum river flow rate (AMRFR) was found to be positively correlated with plantation cover. Reducing plantation land cover from 20 to 10% was found to lead to a modelled 38% reduction in median AMRFR. AMRFR with return periods greater than 10 years were found to be negatively correlated with wetland farming land cover, suggesting that rice paddies play an important role in attenuating extreme river flow events. Nevertheless, the Kolmogorov–Smirnov tests revealed that built land cover is the most important factor defining whether or not an area is likely to report flood disasters in West Java. This is presumably because the more built land cover, the more people available to experience and report flood disasters. Our findings also suggest that more research is needed to understand the important role of plantation cover in aggravating median annual maximum river flow rates and wetland farming cover in mitigating extreme river flow events.

A multi-centre retrospective study of Nocardia speciation and antimicrobial susceptibility in Queensland, Australia - B. Z. Sim; L. Aaron; C. Coulter; J. Parkes-Smith; T. Badrick; K. May; M. Armstrong; S. Hendry; L. Sundac; L. Dang; J. Ho; J. Hanson; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Latitudinal patterns of egg size and maternal investment trade‐offs in reef corals - Nataly Gutierrez‐Isaza; Eugenia M. Sampayo; Catherine E. Lovelock; Steven J. Dalton; Carrie A. Sims; Selina Ward; John M. Pandolfi (Global Ecology and Biogeography, 2023)
Aim The aims were to test the role of temperature in latitudinal patterns of egg size and investigate maternal investment trade‐offs among coral taxa. Location Global, from 34° S to 34° N. Time period 1981–2020. Major taxa studied Reef coral species from the order Scleractinia. Methods We compiled a comprehensive geo‐referenced global dataset of egg sizes (diameter or volume) and fecundity (number of eggs per area) for colonial corals (Scleractinia; 123 species, 5359 observations and 39 localities), substantially enhanced by new field collections (>88% of observations). We used Bayesian phylogenetic multilevel models to test for Rass' rule (a hypothesized negative relationship between egg size and temperature); we also included other environmental variables and life history traits. We also tested whether a trade‐off exists between egg size and fecundity in broadcast spawning hermaphroditic corals with horizontal symbiont transmission (HHT). Results We found a significant relationship between coral egg size and symbiont transmission. Eggs from coral species with vertical symbiont transmission were c . 18.8% smaller than those from species with horizontal symbiont transmission. We also found non‐significant relationships between egg size and sea surface temperature (SST) for broadcast spawning corals and between egg size and fecundity specifically for HHT species. Main conclusions Contrary to recognized latitudinal patterns of egg size across taxa, our study does not provide support for Rass' rule in corals. Additionally, our findings do not support a maternal investment trade‐off between egg size and fecundity for HHT species. Our study used a phylogenetic framework that should be a standard practice when studying interspecific variation, including investigation of maternal investment and identification of the influence of multiple predictors on larval fitness (egg size), in addition to trade‐offs affecting propagule influx (fecundity). Both these functional traits are vital and have direct consequences for population maintenance and connectivity in sessile organisms, such as corals.

Addressing data gaps in marine litter distribution: Citizen science observation of plastics in coastal ecosystems by high-school students - Ana I. Catarino; Edem Mahu; Marine I. Severin; Lazare Kouame Akpetou; Pavanee Annasawmy; Francis Emile Asuquo; Fiona Beckman; Mostapha Benomar; Annette Jaya-Ram; Mohammed Malouli; Jan Mees; Ivanice Monteiro; et al. (Frontiers in Marine Science, 2023)
The Citizen Observation of Local Litter in coastal ECosysTems (COLLECT) project (2021-2022) is a citizen science initiative, supported by the Partnership for Observation of the Global Ocean (POGO), which aimed to acquire distribution and abundance data of coastal plastic litter in seven countries: in Africa (Benin, Cabo Verde, Côte d’Ivoire, Ghana, Morocco, Nigeria) and Asia (Malaysia). In this paper, we describe the workflow used to establish and run this project, as well as the methodologies to acquire data. The COLLECT project consisted of training local students (15 - 18 years old) from ten second cycle institutions (“high schools”) on sampling and analyzing macro-, meso- and microplastics in beach sediments, using a quantitative assessment protocol. We further describe in detail the methodologies applied in assessing the impact of participating in the activities from a social sciences perspective. All documents and materials resulting from this project will be open access and available according to the FAIR Principles (Findable, Accessible, Interoperable, and Reusable). The results and outcomes from COLLECT will contribute to expanding knowledge and establishing baseline information on coastal plastic pollution, with citizen science being an enabler of open science, allowing data to be freely available to the public, academics and policymakers. Expected results from the use of the COLLECT protocol globally will further contribute to the identification of hotspots of coastal plastic litter, and bring awareness to local communities on the potential consequences of plastic pollution. The COLLECT project actively contributes with data suitable to survey plastic litter to the United Nations’ Sustainable Development Goals (UN SDGs), in particular to SDG 14, on the sustainable use of the ocean.

A robust fluorescence-based assay for human erythrocyte Ca++ efflux suitable for high-throughput inhibitor screens - Jeremiah N. Sims; EJun Yun; Jonathan Chu; Mansoor A. Siddiqui; Sanjay A. Desai (European Biophysics Journal, 2023)

Molecular and morphological analysis of Biddulphia sensu lato: a new diagnosis of Biddulphia, with a description of the new genera Biddulphiella and Neobrightwellia - Patricia A. Sims; Matt P. Ashworth; Edward C. Theriot; Schonna R. Manning (Marine Micropaleontology, 2023)

EGR3 regulates opioid-related nociception and motivation in male rats - Swarup Mitra; Shruthi A. Thomas; Jennifer A. Martin; Jamal Williams; Kristen Woodhouse; Ramesh Chandra; Jun Xu Li; Mary Kay Lobo; Fraser J. Sim; David M. Dietz (Psychopharmacology, 2022)

A Fishy Story Promoting a False Dichotomy to Policy-Makers: It Is Not Freshwater vs. Marine Aquaculture - Barry Antonio Costa-Pierce; Abigail B. Bockus; Bela H. Buck; Sander W. K. van den Burg; Thierry Chopin; Joao G. Ferreira; Nils Goseberg; Kevin G. Heasman; Johan Johansen; Sandra E. Shumway; Neil A. Sims; Albert G. J. Tacon (Reviews in Fisheries Science & Aquaculture, 2022)

Mapping mangrove alliances using historical data in Fiji - Brent A. Murray; Neil Sims; Joni Storie (Journal of Coastal Conservation, 2022)

Nitrate enrichment has lineage specific effects on Pocillopora acuta adults, but no transgenerational effects in planulae - Marie E. Strader; Lauren I. Howe-Kerr; Jordan A. Sims; Kelly E. Speare; Amanda N. Shore; Deron E. Burkepile; Adrienne M. S. Correa (Coral Reefs, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Tropical macrophytes promote phytoplankton community shifts in lake mesocosms: relevance for lake restoration in warm climates - Darren Z. H. Sim; Maxine A. D. Mowe; Yiluan Song; Joy Lu; Hugh T. W. Tan; Simon M. Mitrovic; Daniel L. Roelke; Darren C. J. Yeo (Hydrobiologia, 2021)

Reparative System Arising from CCR2(+) Monocyte Conversion Attenuates Neuroinflammation Following Ischemic Stroke - Joohyun Park; Jong Youl Kim; Yu Rim Kim; Meiying Huang; Ji Young Chang; A Young Sim; Hosung Jung; Won Taek Lee; Young-Min Hyun; Jong Eun Lee (Translational Stroke Research, 2021)
Monocytes recruitment from the blood to inflamed tissues following ischemic stroke is an important immune response to wound healing and tissue repair. Mouse monocytes can be endogenously divided into two distinct populations: pro-inflammatory or classical monocytes that express CCR2 high CX3CR1 low and circulate in blood, and anti-inflammatory or non-classical monocytes that express CCR2 low CX3CR1 high and patrol locally. In this study of transgenic mice with functional CX3CR1 GFP/+ or CX3CR1 GFP/+ -CCR2 RFP/+ , we found that CCR2 high CX3CR1 low monocytes recruited to the injured brain were cytokine-dependently converted into CCR2 low CX3CR1 high macrophages, especially under the influence of IL-4 and IL-13, thereby attenuating the neuroinflammation following sterile ischemic stroke. The overall data suggest that (1) the regulation of monocyte-switching is one of the ultimate reparative strategies in ischemic stroke, and (2) the adaptation of monocytes in a locally inflamed milieu is vital to alleviating the effects of ischemic stroke through innate immunity.

Meta‐Fish‐Lib : A generalised, dynamic DNA reference library pipeline for metabarcoding of fishes - Rupert A. Collins; Giulia Trauzzi; Katherine M. Maltby; Thomas I. Gibson; Frances C. Ratcliffe; Jane Hallam; Sophie Rainbird; James Maclaine; Peter A. Henderson; David W. Sims; Stefano Mariani; Martin J. Genner (Journal of Fish Biology, 2021)
The accuracy and reliability of DNA metabarcoding analyses depend on the breadth and quality of the reference libraries that underpin them. However, there are limited options available to obtain and curate the huge volumes of sequence data that are available on public repositories such as NCBI and BOLD. Here, we provide a pipeline to download, clean and annotate mitochondrial DNA sequence data for a given list of fish species. Features of this pipeline include (a) support for multiple metabarcode markers; (b) searches on species synonyms and taxonomic name validation; (c) phylogeny assisted quality control for identification and removal of misannotated sequences; (d) automatically generated coverage reports for each new GenBank release update; and (e) citable, versioned DOIs. As an example we provide a ready‐to‐use curated reference library for the marine and freshwater fishes of the U.K. To augment this reference library for environmental DNA metabarcoding specifically, we generated 241 new MiFish‐12S sequences for 88 U.K. marine species, and make available new primer sets useful for sequencing these. This brings the coverage of common U.K. species for the MiFish‐12S fragment to 93%, opening new avenues for scaling up fish metabarcoding across wide spatial gradients. The Meta‐Fish‐Lib reference library and pipeline is hosted at https://github.com/genner-lab/meta-fish-lib .

Corrigendum: On a Reef Far, Far Away: Anthropogenic Impacts Following Extreme Storms Affect Sponge Health and Bacterial Communities - Amanda Shore; Jordan A. Sims; Michael Grimes; Lauren I. Howe-Kerr; Carsten G. B. Grupstra; Shawn M. Doyle; Lauren Stadler; Jason B. Sylvan; Kathryn E. F. Shamberger; Sarah W. Davies; Lory Z. Santiago-Vázquez; Adrienne M. S. Correa (Frontiers in Marine Science, 2021)

Longevity pathways in stress resistance: targeting NAD and sirtuins to treat the pathophysiology of hemorrhagic shock - Carrie A. Sims; Hanna E. Labiner; Sohini S. Shah; Joseph A. Baur (GeroScience, 2021)

On a Reef Far, Far Away: Anthropogenic Impacts Following Extreme Storms Affect Sponge Health and Bacterial Communities - Amanda Shore; Jordan A. Sims; Michael Grimes; Lauren I. Howe-Kerr; Carsten G. B. Grupstra; Shawn M. Doyle; Lauren Stadler; Jason B. Sylvan; Kathryn E. F. Shamberger; Sarah W. Davies; Lory Z. Santiago-Vázquez; Adrienne M. S. Correa (Frontiers in Marine Science, 2021)
Terrestrial runoff can negatively impact marine ecosystems through stressors including excess nutrients, freshwater, sediments, and contaminants. Severe storms, which are increasing with global climate change, generate massive inputs of runoff over short timescales (hours to days); such runoff impacted offshore reefs in the northwest Gulf of Mexico (NW GoM) following severe storms in 2016 and 2017. Several weeks after coastal flooding from these events, NW GoM reef corals, sponges, and other benthic invertebrates ∼185 km offshore experienced mortality (2016 only) and/or sub-lethal stress (both years). To assess the impact of storm-derived runoff on reef filter feeders, we characterized the bacterial communities of two sponges, Agelas clathrodes and Xestospongia muta , from offshore reefs during periods of sub-lethal stress and no stress over a three-year period (2016—2018). Sponge-associated and seawater-associated bacterial communities were altered during both flood years. Additionally, we found evidence of wastewater contamination (based on 16S rRNA gene libraries and quantitative PCR) in offshore sponge samples, but not in seawater samples, following these flood years. Signs of wastewater contamination were absent during the no-flood year. We show that flood events from severe storms have the capacity to reach offshore reef ecosystems and impact resident benthic organisms. Such impacts are most readily detected if baseline data on organismal physiology and associated microbiome composition are available. This highlights the need for molecular and microbial time series of benthic organisms in near- and offshore reef ecosystems, and the continued mitigation of stormwater runoff and climate change impacts.

Gender differences in respiratory health outcomes among farming cohorts around the globe: findings from the AGRICOH consortium - Jonathan Fix; Isabella Annesi-Maesano; Isabelle Baldi; Mathilde Boulanger; Soo Cheng; Sandra Cortes; Jean- Charles Dalphin; Mohamed Aqiel Dalvie; Bruno Degano; Jeroen Douwes; Wijnand Eduard; Grethe Elholm; et al. (Journal of Agromedicine, 2021)

Impact of formulary interventions on the minimum inhibitory concentration of methicillin-resistant Staphylococcus aureus to mupirocin, chlorhexidine, and octenidine in a Singapore tertiary institution - Shuwei Zheng; S. J. Chung; H. C. J. Sim; T. M. Chlebicka; Y. H. Chan; T. P. Lim; L. H. A. Kwa; M. P. Chlebicki (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Nitrogen Fertilizer Rate Affects Yield and Tuber Quality of Drip-Irrigated Tablestock Potatoes (Solanum tuberosum L.) Grown under Subtropical Conditions - Mildred N. Makani; Lincoln Zotarelli; Steven A. Sargent; Donald J. Huber; Charles A. Sims (American Journal of Potato Research, 2020)

Kappa opioid receptors mediate an initial aversive component of paclitaxel-induced neuropathy - Julie A. Meade; Y. Alkhlaif; K. M. Contreras; S. Obeng; W. Toma; L. J. Sim-Selley; D. E. Selley; M. I. Damaj (Psychopharmacology, 2020)

Correction to: CpG‑creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)

CpG-creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)
Mutations can occur throughout the virus genome and may be beneficial, neutral or deleterious. We are interested in mutations that yield a C next to a G, producing CpG sites. CpG sites are rare in eukaryotic and viral genomes. For the eukaryotes, it is thought that CpG sites are rare because they are prone to mutation when methylated. In viruses, we know less about why CpG sites are rare. A previous study in HIV suggested that CpG-creating transition mutations are more costly than similar non-CpG-creating mutations. To determine if this is the case in other viruses, we analyzed the allele frequencies of CpG-creating and non-CpG-creating mutations across various strains, subtypes, and genes of viruses using existing data obtained from Genbank, HIV Databases, and Virus Pathogen Resource. Our results suggest that CpG sites are indeed costly for most viruses. By understanding the cost of CpG sites, we can obtain further insights into the evolution and adaptation of viruses.

Patch size drives settlement success and spatial distribution of coral larvae under space limitation - E. M. Sampayo; G. Roff; C. A. Sims; P. G. Rachello-Dolmen; J. M. Pandolfi (Coral Reefs, 2020)

Overhauling Ocean Spatial Planning to Improve Marine Megafauna Conservation - Ana Micaela Martins Sequeira; Graeme Clive Hays; David W. Sims; Víctor M. Eguíluz; Jorge P. Rodríguez; Michelle R. Heupel; Rob Harcourt; Hannah Calich; Nuno Queiroz; Daniel Paul Costa; Juan Fernández-Gracia; Luciana C. Ferreira; et al. (Frontiers in Marine Science, 2019)

Refugia under threat: Mass bleaching of coral assemblages in high‐latitude eastern Australia - Sun W. Kim; Eugenia M. Sampayo; Brigitte Sommer; Carrie A. Sims; Maria del C. Gómez‐Cabrera; Steve J. Dalton; Maria Beger; Hamish A. Malcolm; Renata Ferrari; Nicola Fraser; Will F. Figueira; Stephen D. A. Smith; et al. (Global Change Biology, 2019)
Environmental anomalies that trigger adverse physiological responses and mortality are occurring with increasing frequency due to climate change. At species' range peripheries, environmental anomalies are particularly concerning because species often exist at their environmental tolerance limits and may not be able to migrate to escape unfavourable conditions. Here, we investigated the bleaching response and mortality of 14 coral genera across high‐latitude eastern Australia during a global heat stress event in 2016. We evaluated whether the severity of assemblage‐scale and genus‐level bleaching responses was associated with cumulative heat stress and/or local environmental history, including long‐term mean temperatures during the hottest month of each year (SST LTMAX ), and annual fluctuations in water temperature (SST VAR ) and solar irradiance (PARZ VAR ). The most severely‐bleached genera included species that were either endemic to the region ( Pocillopora aliciae ) or rare in the tropics (e.g. Porites heronensis ). Pocillopora spp., in particular, showed high rates of immediate mortality. Bleaching severity of Pocillopora was high where SST LTMAX was low or PARZ VAR was high, whereas bleaching severity of Porites was directly associated with cumulative heat stress. While many tropical Acropora species are extremely vulnerable to bleaching, the Acropora species common at high latitudes, such as A. glauca and A. solitaryensis , showed little incidence of bleaching and immediate mortality. Two other regionally‐abundant genera, Goniastrea and Turbinaria , were also largely unaffected by the thermal anomaly. The severity of assemblage‐scale bleaching responses was poorly explained by the environmental parameters we examined. Instead, the severity of assemblage‐scale bleaching was associated with local differences in species abundance and taxon‐specific bleaching responses. The marked taxonomic disparity in bleaching severity, coupled with high mortality of high‐latitude endemics, point to climate‐driven simplification of assemblage structures and progressive homogenisation of reef functions at these high‐latitude locations.

Changes in local free-living parasite populations in response to cleaner manipulation over 12 years - A. S. Grutter; S. P. Blomberg; S. Box; R. Bshary; O. Ho; E. M. P. Madin; E. C. McClure; M. G. Meekan; J. M. Murphy; M. A. Richardson; P. C. Sikkel; C. A. Sims; et al. (Oecologia, 2019)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Iron considerations for the athlete: a narrative review - Marc Sim; Laura A. Garvican-Lewis; Gregory R. Cox; Andrew Govus; Alannah K. A. McKay; Trent Stellingwerff; Peter Peeling (European Journal of Applied Physiology, 2019)

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Practical Approaches and Advances in Spatial Tools to Achieve Multi-Objective Marine Spatial Planning - Amanda T. Lombard; Natalie C. Ban; Joanna L. Smith; Sarah E. Lester; Kerry J. Sink; Spencer A. Wood; Aerin L. Jacob; Zacharoula Kyriazi; Richard Tingey; Helena E. Sims (Frontiers in Marine Science, 2019)

Climatically driven changes in primary production propagate through trophic levels - David C. Stoner; Joseph O. Sexton; David M. Choate; Jyothy Nagol; Heather H. Bernales; Steven A. Sims; Kirsten E. Ironside; Kathleen M. Longshore; Thomas C. Edwards (Global Change Biology, 2018)
Climate and land‐use change are the major drivers of global biodiversity loss. Their effects are particularly acute for wide‐ranging consumers, but little is known about how these factors interact to affect the abundance of large carnivores and their herbivore prey. We analyzed population densities of a primary and secondary consumer (mule deer, Odocoileus hemionus , and mountain lion, Puma concolor ) across a climatic gradient in western North America by combining satellite‐based maps of plant productivity with estimates of animal abundance and foraging area derived from Global Positioning Systems telemetry data (GPS). Mule deer density exhibited a positive, linear relationship with plant productivity ( r 2 = 0.58), varying by a factor of 18 across the climate‐vegetation gradient (range: 38–697 individuals/100 km 2 ). Mountain lion home range size decreased in response to increasing primary productivity and consequent changes in the abundance of their herbivore prey (range: 20–450 km 2 ). This pattern resulted in a strong, positive association between plant productivity and mountain lion density ( r 2 = 0.67). Despite varying densities, the ratio of prey to predator remained constant across the climatic gradient (mean ± SE = 363 ± 29 mule deer/mountain lion), suggesting that the determinacy of the effect of primary productivity on consumer density was conserved across trophic levels. As droughts and longer term climate changes reduce the suitability of marginal habitats, consumer home ranges will expand in order for individuals to meet basic nutritional requirements. These changes portend decreases in the abundance of large‐bodied, wide‐ranging wildlife through climatically driven reductions in carrying capacity, as well as increased human–wildlife interactions stemming from anthropogenic land use and habitat fragmentation.

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Trade-offs between defence and competition in gregarious juvenile fluted giant clams (Tridacna squamosa L.) - Darren Z. H. Sim; Mei Lin Neo; Ambert C. F. Ang; Lynette S. M. Ying; Peter A. Todd (Marine Biology, 2018)

Fungal and herbivore elicitation of the novel maize sesquiterpenoid, zealexin A4, is attenuated by elevated CO2 - Shawn A. Christensen; Alisa Huffaker; James Sims; Charles T. Hunter; Anna Block; Martha M. Vaughan; Denis Willett; Maritza Romero; J. Erik Mylroie; W. Paul Williams; Eric A. Schmelz (Planta, 2018)

Predicting the risk of cucurbit downy mildew in the eastern United States using an integrated aerobiological model - K. N. Neufeld; A. P. Keinath; B. K. Gugino; M. T. McGrath; E. J. Sikora; S. A. Miller; M. L. Ivey; D. B. Langston; B. Dutta; T. Keever; A. Sims; P. S. Ojiambo (International Journal of Biometeorology, 2018)

An analysis of first-time and repeat visitors to Korean national parks from 2007 and 2013 - Yunseon Choe; Michael A. Schuett; Kyu-Won Sim (Journal of Mountain Science, 2017)

Age estimates of Frullania (Frullaniaceae, Porellales) main lineages: another example of rapid and recent diversification in liverwort evolution - Sara E. Silva; Diogo N. Silva; Tereza Almeida; CÉsar A. Garcia; OctÁvio S. Paulo; Manuela Sim-sim (Systematics and Biodiversity, 2017)

Differential expression of store-operated calcium- and proliferation-related genes in hepatocellular carcinoma cells following TRPC1 ion channel silencing - Cigdem Selli; Dominic A. Pearce; Andrew H. Sims; Metiner Tosun (Molecular and Cellular Biochemistry, 2016)

Decision theory, motor planning, and visual memory: deciding where to reach when memory errors are costly - Rachel A. Lerch; Chris R. Sims (Experimental Brain Research, 2016)

Is there a relationship between PPARD T294C/PPARGC1A Gly482Ser variations and physical endurance performance in the Korean population? - Han-Jun Jin; In-Wook Hwang; Ki-Cheol Kim; Hyun-Ik Cho; Tae-Hwan Park; Yun-A Shin; Ho-Seong Lee; Ji-Hyun Hwang; Ah-Ram Kim; Kwang-Hee Lee; Ye-Eun Shin; Ji-Yeon Lee; et al. (Genes & Genomics, 2016)

Short-term response and recovery of bluebells (Hyacinthoides non-scripta) after rooting by wild boar (Sus scrofa) - Natasha K. Sims; Elizabeth A. John; Alan J. A. Stewart (Plant Ecology, 2014)

Warming-Induced Shrub Expansion and Lichen Decline in the Western Canadian Arctic - Robert H. Fraser; Trevor C. Lantz; Ian Olthof; Steven V. Kokelj; Richard A. Sims (Ecosystems, 2014)

An analysis of the sponge Acanthostrongylophora igens' microbiome yields an actinomycete that produces the natural product manzamine A - Amanda L. Waters; Olivier Peraud; Noer Kasanah; James W. Sims; Nuwan Kothalawala; Matthew A. Anderson; Samuel H. Abbas; Karumanchi V. Rao; Vijay R. Jupally; Michelle Kelly; Amala Dass; Russell T. Hill; et al. (Frontiers in Marine Science, 2014)

An improved approach for remotely sensing water stress impacts on forest C uptake - Daniel A. Sims; Edward R. Brzostek; Abdullah F. Rahman; Danilo Dragoni; Richard P. Phillips (Global Change Biology, 2014)
Given that forests represent the primary terrestrial sink for atmospheric CO 2 , projections of future carbon (C) storage hinge on forest responses to climate variation. Models of gross primary production ( GPP ) responses to water stress are commonly based on remotely sensed changes in canopy ‘greenness’ (e.g., normalized difference vegetation index; NDVI ). However, many forests have low spectral sensitivity to water stress ( SSWS ) – defined here as drought‐induced decline in GPP without a change in greenness. Current satellite‐derived estimates of GPP use a vapor pressure deficit ( VPD ) scalar to account for the low SWSS of forests, but fail to capture their responses to water stress. Our objectives were to characterize differences in SSWS among forested and nonforested ecosystems, and to develop an improved framework for predicting the impacts of water stress on GPP in forests with low SSWS . First, we paired two independent drought indices with NDVI data for the conterminous US from 2000 to 2011, and examined the relationship between water stress and NDVI . We found that forests had lower SSWS than nonforests regardless of drought index or duration. We then compared satellite‐derived estimates of GPP with eddy‐covariance observations of GPP in two deciduous broadleaf forests with low SSWS : the Missouri Ozark ( MO ) and Morgan Monroe State Forest ( MMSF ) AmeriFlux sites. Model estimates of GPP that used VPD scalars were poorly correlated with observations of GPP at MO ( r 2 = 0.09) and MMSF ( r 2 = 0.38). When we included the NDVI responses to water stress of adjacent ecosystems with high SSWS into a model based solely on temperature and greenness, we substantially improved predictions of GPP at MO ( r 2 = 0.83) and for a severe drought year at the MMSF ( r 2 = 0.82). Collectively, our results suggest that large‐scale estimates of GPP that capture variation in SSWS among ecosystems could improve predictions of C uptake by forests under drought.

Chronic water stress reduces tree growth and the carbon sink of deciduous hardwood forests - Edward R. Brzostek; Danilo Dragoni; Hans Peter Schmid; Abdullah F. Rahman; Daniel Sims; Craig A. Wayson; Daniel J. Johnson; Richard P. Phillips (Global Change Biology, 2014)
Predicted decreases in water availability across the temperate forest biome have the potential to offset gains in carbon (C) uptake from phenology trends, rising atmospheric CO 2 , and nitrogen deposition. While it is well established that severe droughts reduce the C sink of forests by inducing tree mortality, the impacts of mild but chronic water stress on forest phenology and physiology are largely unknown. We quantified the C consequences of chronic water stress using a 13‐year record of tree growth ( n = 200 trees), soil moisture, and ecosystem C balance at the Morgan–Monroe State Forest ( MMSF ) in Indiana, and a regional 11‐year record of tree growth ( n > 300 000 trees) and water availability for the 20 most dominant deciduous broadleaf tree species across the eastern and midwestern USA . We show that despite ~26 more days of C assimilation by trees at the MMSF , increasing water stress decreased the number of days of wood production by ~42 days over the same period, reducing the annual accrual of C in woody biomass by 41%. Across the deciduous forest region, water stress induced similar declines in tree growth, particularly for water‐demanding ‘mesophytic’ tree species. Given the current replacement of water‐stress adapted ‘xerophytic’ tree species by mesophytic tree species, we estimate that chronic water stress has the potential to decrease the C sink of deciduous forests by up to 17% (0.04 Pg C yr −1 ) in the coming decades. This reduction in the C sink due to mesophication and chronic water stress is equivalent to an additional 1–3 days of global C emissions from fossil fuel burning each year. Collectively, our results indicate that regional declines in water availability may offset the growth‐enhancing effects of other global changes and reduce the extent to which forests ameliorate climate warming.

Conservation of Portuguese red-listed bryophytes species in Portugal: Promoting a shift in perspective on climate changes - C. Sérgio; C. A. Garcia; C. Vieira; H. Hespanhol; M. Sim-Sim; S. Stow; R. Figueira (Plant Biosystems, 2014)

Isolation and characterization of 8 polymorphic microsatellite markers from the Greater Short-horned Lizard (Phrynosoma hernandesi) - Zijian Sim; Brandon K. Booker; Michelle Viengkone; Corey S. Davis; Magdalene N.-Y. Leung; Anthony P. Russell; Cynthia A. Paszkowski (Conservation Genetics Resources, 2014)

Snapper ( Chrysophrys auratus ): a review of life history and key vulnerabilities in New Zealand - DM Parsons; CJ Sim‐Smith; M Cryer; MP Francis; B Hartill; EG Jones; A Le Port; M Lowe; J McKenzie; M Morrison; LJ Paul; C Radford; et al. (New Zealand Journal of Marine and Freshwater Research, 2014)
Snapper ( Chrysophrys auratus ) is an important coastal fish species in New Zealand for a variety of reasons, but the large amount of research conducted on snapper has not been reviewed. Here, we review life history information and potential threats for snapper in New Zealand. We present information on snapper life history, defining stages (eggs and larvae, juvenile and adult), and assess potential threats and knowledge gaps. Overall we identify six key points: 1. post‐settlement snapper are highly associated with certain estuarine habitats that are under threat from land‐based stressors. This may serve as a bottleneck for snapper populations; 2. the largest knowledge gaps relate to the eggs and larvae. Additional knowledge may help to anticipate the effects of climate change, which will likely have the greatest influence on these early life stages; 3. ocean acidification, from land‐based sources and from climate change, may be an important threat to larval snapper; 4. a greater understanding of population connectivity would improve certainty around the sustainability of fishery exploitation; 5. the collateral effects of fishing are likely to be relevant to fishery productivity, ecosystem integrity and enduser value; 6. our understanding of the interrelationships between snapper and other ecosystem components is still deficient.

Cleaning up the biogeography of Labroides dimidiatus using phylogenetics and morphometrics - C. A. Sims; C. Riginos; S. P. Blomberg; T. Huelsken; J. Drew; A. S. Grutter (Coral Reefs, 2014)

Seasonal abundance, philopatry and demographic structure of Caribbean reef shark (Carcharhinus perezi) assemblages in the north-east Exuma Sound, The Bahamas - Edward J. Brooks; David W. Sims; Andy J. Danylchuk; Katherine A. Sloman (Marine Biology, 2013)

Estimating traveler populations at airport and cruise terminals for population distribution and dynamics - Warren C. Jochem; Kelly Sims; Edward A. Bright; Marie L. Urban; Amy N. Rose; Phillip R. Coleman; Budhendra L. Bhaduri (Natural Hazards, 2013)

Inferred global connectivity of whale shark Rhincodon typus populations - A. M. M. Sequeira; C. Mellin; M. G. Meekan; D. W. Sims; C. J. A. Bradshaw (Journal of Fish Biology, 2013)
Ten years have passed since the last synopsis of whale shark Rhincodon typus biogeography. While a recent review of the species' biology and ecology summarized the vast data collected since then, it is clear that information on population geographic connectivity, migration and demography of R. typus is still limited and scattered. Understanding R. typus migratory behaviour is central to its conservation management considering the genetic evidence suggesting local aggregations are connected at the generational scale over entire ocean basins. By collating available data on sightings, tracked movements and distribution information, this review provides evidence for the hypothesis of broad‐scale connectivity among populations, and generates a model describing how the world's R. typus are part of a single, global meta‐population. Rhincodon typus occurrence timings and distribution patterns make possible a connection between several aggregation sites in the Indian Ocean. The present conceptual model and validating data lend support to the hypothesis that R. typus are able to move among the three largest ocean basins with a minimum total travelling time of around 2–4 years. The model provides a worldwide perspective of possible R. typus migration routes, and suggests a modified focus for additional research to test its predictions. The framework can be used to trim the hypotheses for R. typus movements and aggregation timings, thereby isolating possible mating and breeding areas that are currently unknown. This will assist endeavours to predict the longer‐term response of the species to ocean warming and changing patterns of human‐induced mortality.

Transcriptional response of Pseudomonas aeruginosa to a phosphate-deficient Lolium perenne rhizosphere - Agnieszka Zyśko; Hervé Sanguin; Andrew Hayes; Leanne Wardleworth; Leo A. H. Zeef; Allan Sim; Eric Paterson; Brajesh K. Singh; Michael A. Kertesz (Plant and Soil, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

A Classification of Floodplains and Wetlands of the Murray-Darling Basin Based on Changes in Flows Following Water Resource Development - Neil C. Sims; Anthony A. Chariton; Huidong Jin; Matthew J. Colloff (Wetlands, 2012)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

∆9-Tetrahydrocannabinol-dependent mice undergoing withdrawal display impaired spatial memory - Laura E. Wise; Stephen A. Varvel; Dana E. Selley; Jason M. Wiebelhaus; Kelly A. Long; Lisa S. Middleton; Laura J. Sim-Selley; Aron H. Lichtman (Psychopharmacology, 2011)

Evaluation of methods to determine residual soil nitrate zones across the northern Great Plains of the USA - D. Franzen; D. Long; A. Sims; J. Lamb; F. Casey; J. Staricka; M. Halvorson; V. Hofman (Precision Agriculture, 2011)

Inhibition of Helicobacter pylori adhesion to Kato III cells by intact and low molecular weight acharan sulfate - Joon-Soo Sim; Bum-Soo Hahn; A-Rang Im; Youmie Park; Ji-Eun Shin; Eun-Ah Bae; Dong-Hyun Kim; Yeong Shik Kim (Glycoconjugate Journal, 2011)

Introduction of 2,4-dichlorophenoxyacetic acid into soil with solvents and resulting implications for bioavailability to microorganisms - Teresa A. Johnson; Gerald K. Sims (World Journal of Microbiology and Biotechnology, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

The ability of a benthic elasmobranch to discriminate between biological and artificial electric fields - Joel A. Kimber; David W. Sims; Patricia H. Bellamy; Andrew B. Gill (Marine Biology, 2011)

Variability in Light-Use Efficiency for Gross Primary Productivity on Great Plains Grasslands - H. Wayne Polley; Rebecca L. Phillips; Albert B. Frank; James A. Bradford; Phillip L. Sims; Jack A. Morgan; James R. Kiniry (Ecosystems, 2011)

Tree-pulling experiment: an analysis into the mechanical stability of rain trees - Lai Fern Ow; F. R. Harnas; I. G. B. Indrawan; A. Sahadewa; E. K. Sim; H. Rahardjo; E. C. Leong; Y. K. Fong; P. Y. Tan (Trees, 2010)

Diurnal variation of precipitation over the Carolina Sandhills region - A. Wootten; S. Raman; A. Sims (Journal of Earth System Science, 2010)

Increased P2X7R expression in atrial cardiomyocytes of caveolin-1 deficient mice - K. Barth; C. Pfleger; A. Linge; J. A. Sim; A. Surprenant; N. Steinbronn; R. H. Strasser; M. Kasper (Histochemistry and Cell Biology, 2010)

Molecular, phytochemical and morphological characterization of the liverwort genus Radula in Portugal (mainland, Madeira, Azores) - Michael Stech; Manuela Sim-Sim; M. Glória Esquível; Leena luís; Susana Fontinha; Carlos Lobo; César Garcia; Soraia Martins; Cristiana Vieira; José Barroso; Luis G. Pedro; A. Cristina S. Figueiredo (Systematics and Biodiversity, 2010)

Physiological and environmental regulation of interannual variability in CO 2 exchange on rangelands in the western United States - H. WAYNE POLLEY; WILLIAM EMMERICH; JAMES A. BRADFORD; PHILLIP L. SIMS; DOUGLAS A. JOHNSON; NICANOR Z. SALIENDRA; TONY SVEJCAR; RAYMOND ANGELL; ALBERT B. FRANK; REBECCA L. PHILLIPS; KEIRITH A. SNYDER; JACK A. MORGAN (Global Change Biology, 2010)
For most ecosystems, net ecosystem exchange of CO 2 (NEE) varies within and among years in response to environmental change. We analyzed measurements of CO 2 exchange from eight native rangeland ecosystems in the western United States (58 site‐years of data) in order to determine the contributions of photosynthetic and respiratory (physiological) components of CO 2 exchange to environmentally caused variation in NEE. Rangelands included Great Plains grasslands, desert shrubland, desert grasslands, and sagebrush steppe. We predicted that (1) week‐to‐week change in NEE and among‐year variation in the response of NEE to temperature, net radiation, and other environmental drivers would be better explained by change in maximum rates of ecosystem photosynthesis ( A max ) than by change in apparent light‐use efficiency ( α ) or ecosystem respiration at 10 °C ( R 10 ) and (2) among‐year variation in the responses of NEE, A max , and α to environmental drivers would be explained by changes in leaf area index (LAI). As predicted, NEE was better correlated with A max than α or R 10 for six of the eight rangelands. Week‐to‐week variation in NEE and physiological parameters correlated mainly with time‐lagged indices of precipitation and water‐related environmental variables, like potential evapotranspiration, for desert sites and with net radiation and temperature for Great Plains grasslands. For most rangelands, the response of NEE to a given change in temperature, net radiation, or evaporative demand differed among years because the response of photosynthetic parameters ( A max , α ) to environmental drivers differed among years. Differences in photosynthetic responses were not explained by variation in LAI alone. A better understanding of controls on canopy photosynthesis will be required to predict variation in NEE of rangeland ecosystems.

Glycosaminoglycans from earthworms (Eisenia andrei) - A-Rang Im; Youmie Park; Joon-Soo Sim; Zhenqing Zhang; Zhenling Liu; Robert J. Linhardt; Yeong Shik Kim (Glycoconjugate Journal, 2010)

The role of learning in shark behaviour - Tristan L Guttridge; Arthur A Myrberg; Ila F Porcher; David W Sims; Jens Krause (Fish and Fisheries, 2009)
The role of learning in behaviour is well known for many animal taxa, including teleost fishes, insects, birds and mammals. However, its importance to sharks in everyday behavioural processes has rarely been considered. Almost 50 years ago the first learning experiments on sharks were conducted; our first section discusses these studies and places them in a framework of associative and non‐associative learning. These experiments showed that sharks were capable of different forms of learning, such as operant and classical conditioning and habituation. Sharks could learn associations as rapidly as other vertebrates and also remember training regimes for several months. However, much of this experimental evidence was based on small sample sizes and few shark orders, such as Carcharhiniformes and Orectobliformes, leaving large gaps in our knowledge of the general learning capabilities of other shark orders. We also examine recent research that has tested for, or inferred learning in behavioural processes. This section reveals that sharks, like teleost fishes use learning to improve prey search and capture to potentially navigate and orientate in their home range and recognize conspecifics, heterospecifics and mates. Learning is also discussed in relation to ecotourism and fisheries. Findings indicated that these activities may lead to conditioning of sharks and that considerable effort should go into investigating what impact this could have on the shark species involved. Finally, we discuss the importance of combining laboratory experiments with field studies, the use of new experimental techniques, the role of model species and research priorities for future work.

Identification of high-mannose and multiantennary complex-type N-linked glycans containing α-galactose epitopes from Nurse shark IgM heavy chain - David J. Harvey; Max Crispin; Beryl E. Moffatt; Sylvia L. Smith; Robert B. Sim; Pauline M. Rudd; Raymond A. Dwek (Glycoconjugate Journal, 2009)

Expression and Characterization of Human Tissue-Plasminogen Activator in Transgenic Tobacco Plants - Bum-Soo Hahn; Joon-Soo Sim; Hyeong-Mi Kim; Mi-Young Ahn; Hyo-Kyung Pak; Nan-A Kim; Yong-Hwan Kim (Plant Molecular Biology Reporter, 2009)

Pharmacophore based 3D-QSAR study of VEGFR-2 inhibitors - M. M. Neaz; F. A. Pasha; M. Muddassar; So Ha Lee; Taebo Sim; Jung-Mi Hah; Seung Joo Cho (Medicinal Chemistry Research, 2009)

Variation of acharan sulfate and monosaccharide composition and analysis of neutral N-glycans in African giant snail (Achatina fulica) - Youmie Park; Zhenqing Zhang; Tatiana N. Laremore; Boyangzi Li; Joon-Soo Sim; A-Rang Im; Mi Young Ahn; Yeong Shik Kim; Robert J. Linhardt (Glycoconjugate Journal, 2008)

Distribution and symptoms of epiphyte infection in major carrageenophyte-producing farms - Charles S. Vairappan; Chong Sim Chung; A. Q. Hurtado; Flower E. Soya; Genevieve Bleicher Lhonneur; Alan Critchley (Journal of Applied Phycology, 2008)

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Exploration of Ellsworth Subglacial Lake: a concept paper on the development, organisation and execution of an experiment to explore, measure and sample the environment of a West Antarctic subglacial lake - M.J. Siegert; A. Behar; M. Bentley; D. Blake; S. Bowden; P. Christoffersen; C. Cockell; H. Corr; D. C. Cullen; H. Edwards; A. Ellery; C. Ellis-Evans; et al. (Reviews in Environmental Science and Bio/Technology, 2007)

Nitrogen decreases and precipitation increases ectomycorrhizal extramatrical mycelia production in a longleaf pine forest - Stephanie E. Sims; Joseph J. Hendricks; Robert J. Mitchell; Kevin A. Kuehn; Stephen D. Pecot (Mycorrhiza, 2007)

Ecological regime shifts in salinised wetland systems. I. Salinity thresholds for the loss of submerged macrophytes - Lien L. Sim; Jane M. Chambers; Jenny A. Davis (Hydrobiologia, 2006)

Ecological regime shifts in salinised wetland systems. II. Factors affecting the dominance of benthic microbial communities - Lien L. Sim; Jenny A. Davis; Jane M. Chambers (Hydrobiologia, 2006)

Designing Systematic Conservation Assessments that Promote Effective Implementation: Best Practice from South Africa - ANDREW T. KNIGHT; AMANDA DRIVER; RICHARD M. COWLING; KRISTAL MAZE; PHILIP G. DESMET; AMANDA T. LOMBARD; MATHIEU ROUGET; MARK A. BOTHA; ANDRE F. BOSHOFF; J. GUY CASTLEY; PETER S. GOODMAN; KATHY MACKINNON; et al. (Conservation Biology, 2006)
Systematic conservation assessment and conservation planning are two distinct fields of conservation science often confused as one and the same. Systematic conservation assessment is the technical, often computer‐based, identification of priority areas for conservation. Conservation planning is composed of a systematic conservation assessment coupled with processes for development of an implementation strategy and stakeholder collaboration. The peer‐reviewed conservation biology literature abounds with studies analyzing the performance of assessments (e.g., area‐selection techniques). This information alone, however, can never deliver effective conservation action; it informs conservation planning. Examples of how to translate systematic assessment outputs into knowledge and then use them for “doing” conservation are rare. South Africa has received generous international and domestic funding for regional conservation planning since the mid‐1990s. We reviewed eight South African conservation planning processes and identified key ingredients of best practice for undertaking systematic conservation assessments in a way that facilitates implementing conservation action. These key ingredients include the design of conservation planning processes, skills for conservation assessment teams, collaboration with stakeholders, and interpretation and mainstreaming of products (e.g., maps) for stakeholders. Social learning institutions are critical to the successful operationalization of assessments within broader conservation planning processes and should include not only conservation planners but also diverse interest groups, including rural landowners, politicians, and government employees.

Does chemical composition of individual Scots pine trees determine the biodiversity of their associated ground vegetation? - Glenn R. Iason; Jack J. Lennon; Robin J. Pakeman; Vera Thoss; Joan K. Beaton; David A. Sim; David A. Elston (Ecology Letters, 2005)
Despite plant secondary metabolites being major determinants of species interactions and ecosystem processes, their role in the maintenance of biodiversity has received little attention. In order to investigate the relationship between chemical and biological diversity in a natural ecosystem, we considered the impact of chemical diversity in individual Scots pine trees ( Pinus sylvestris ) on species richness of associated ground vegetation. Scots pine trees show substantial genetically determined constitutive variation between individuals in concentrations of a group of secondary metabolites, the monoterpenes. When the monoterpenes of particular trees were assessed individually, there was no relationship with species richness of associated ground flora. However, the chemical diversity of monoterpenes of individual trees was significantly positively associated with the species richness of the ground vegetation beneath each tree, mainly the result of an effect among the non‐woody vascular plants. This correlation suggests that the chemical diversity of the ecosystem dominant species has an important role in shaping the biodiversity of the associated plant community. The extent and significance of this effect, and its underlying processes require further investigation.

The effects of climate variability on zooplankton and basking shark ( Cetorhinus maximus ) relative abundance off southwest Britain - PETER A. COTTON; DAVID W. SIMS; SAM FANSHAWE; MARK CHADWICK (Fisheries Oceanography, 2005)
At small spatial scales basking sharks ( Cetorhinus maximus ) forage selectively on zooplankton along thermal fronts, but the factors influencing broader scale patterns in their abundance and distribution remain largely unknown. Using long‐term sightings data collected off southwest Britain between 1988 and 2001, we show that the number of basking sharks recorded was highly correlated with abiotic factors, principally sea surface temperature (SST) and the lagged effect of SST in the previous month, but only very weakly to zooplankton density. This suggests that the changes in number of basking sharks recorded over large spatio‐temporal scales are more closely related to the availability of climate‐driven thermal resources than prey availability, whereas the converse is supported by previous studies at local scales. Taken together, these results imply scale‐dependent behavioural responses in basking sharks, with small‐scale foraging movements linked by broad scale responses to temperature variation.

Genetic linkage mapping of an annual × perennial ryegrass population - S. E. Warnke; R. E. Barker; Geunhwa Jung; Sung-Chur Sim; M. A. Rouf Mian; M. C. Saha; L. A. Brilman; M. P. Dupal; J. W. Forster (Theoretical and Applied Genetics, 2004)

Molecular evolutionary analysis of the widespread piggyBac transposon family and related "domesticated" sequences - A. Sarkar; C. Sim; Y. S. Hong; J. R. Hogan; M. J. Fraser; H. M. Robertson; F. H. Collins (Molecular Genetics and Genomics, 2003)

Construction of a BAC library and generation of BAC end sequence-tagged connectors for genome sequencing of the African malaria mosquito Anopheles gambiae - Y. S. Hong; J. R. Hogan; X. Wang; A. Sarkar; C. Sim; B. J. Loftus; C. Ren; E. R. Huff; J. L. Carlile; K. Black; H.-B. Zhang; M. J. Gardner; et al. (Molecular Genetics and Genomics, 2003)

Establishing the Link between Ammonia Emission Control and Measurements of Reduced Nitrogen Concentrations and Deposition - Mark A. Sutton; Willem A. H. Asman; Thomas Ellermann; J. A. Van Jaarsveld; Karin Acker; Viney Aneja; Jan Duyzer; Laszlo Horvath; Sergey Paramonov; Marta Mitosinkova; Y. Sim Tang; Beat Achermann; et al. (Environmental Monitoring and Assessment, 2003)

Respiratory symptoms and lung-function changes with exposure to five substances in aluminium smelters - Lin Fritschi; Malcolm R. Sim; Andrew Forbes; Michael J. Abramson; Geza Benke; William A. Musk; Nicholas H. de Klerk (International Archives of Occupational and Environmental Health, 2003)

Analysis of 15 primary open-angle glaucoma families from Australia identifies a founder effect for the Q368STOP mutation of myocilin - Paul N. Baird; Jamie E. Craig; Andrea J. Richardson; Maree A. Ring; Pamela Sim; Sue Stanwix; Simon J. Foote; David A. Mackey (Human Genetics, 2003)

Spring Wheat Response to Fertilizer Nitrogen Following a Sugar Beet Crop Varying in Canopy Color - A. L. Sims; J. T. Moraghan; L. J. Smith (Precision Agriculture, 2002)

Seasonal variability of apoplastic NH4 + and pH in an intensively managed grassland - Benjamin Loubet; Celia Milford; Paul W. Hill; Y. Sim Tang; Pierre Cellier; Mark A. Sutton (Plant and Soil, 2002)

Respiratory symptoms and lung function in bauxite miners - Jeremy R. Beach; Nicholas H. de Klerk; Lin Fritschi; Malcolm R. Sim; A. William Musk; Geza Benke; Michael J. Abramson; John J. McNeil (International Archives of Occupational and Environmental Health, 2001)

Canopy radiation‐ and water‐use efficiencies as affected by elevated [CO 2 ] - Dafeng Hui; Yiqi Luo; Weixin Cheng; J. S. Coleman; Dale W. Johnson; Daniel A. Sims (Global Change Biology, 2001)
Summary This study used an environmentally controlled plant growth facility, EcoCELLs, to measure canopy gas exchanges directly and to examine the effects of elevated [CO 2 ] on canopy radiation‐ and water‐use efficiencies. Sunflowers ( Helianthus annus var. Mammoth) were grown at ambient (399 μmol mol −1 ) and elevated [CO 2 ] (746 μmol mol −1 ) for 53 days in EcoCELLs. Whole canopy carbon‐ and water‐fluxes were measured continuously during the period of the experiment. The results indicated that elevated [CO 2 ] enhanced daily total canopy carbon‐ and water‐fluxes by 53% and 11%, respectively, on a ground‐area basis, resulting in a 54% increase in radiation‐use efficiency (RUE) based on intercepted photosynthetic active radiation and a 26% increase in water‐use efficiency (WUE) by the end of the experiment. Canopy carbon‐ and water‐fluxes at both CO 2 treatments varied with canopy development. They were small at 22 days after planting (DAP) and gradually increased to the maxima at 46 DAP. When canopy carbon‐ and water‐fluxes were expressed on a leaf‐area basis, no effect of CO 2 was found for canopy water‐flux while elevated [CO 2 ] still enhanced canopy carbon‐flux by 29%, on average. Night‐time canopy carbon‐flux was 32% higher at elevated than at ambient [CO 2 ]. In addition, RUE and WUE displayed strong diurnal variations, high at noon and low in the morning or afternoon for WUE but opposite for RUE. This study provided direct evidence that plant canopy may consume more, instead of less, water but utilize both water and radiation more efficiently at elevated than at ambient [CO 2 ], at least during the exponential growth period as illustrated in this experiment.

Photosynthesis, respiration, and net primary production of sunflower stands in ambient and elevated atmospheric CO 2 concentrations: an invariant NPP:GPP ratio? - Weixin Cheng; Daniel A. Sims; Yiqi Luo; James S. Coleman; Dale W. Johnson (Global Change Biology, 2000)
Summary The effect of elevated CO 2 on photosynthesis, respiration, and growth efficiency of sunflower plants at the whole‐stand level was investigated using a whole‐system gas exchange facility (the EcoCELLs at the Desert Research Institute) and a 13 C natural tracer method. Total daily photosynthesis (GPP), net primary production (NPP), and respiration under the elevated CO 2 treatment were consistently higher than under the ambient CO 2 treatment. The overall level of enhancement due to elevated CO 2 was consistent with published results for a typical C3 plant species. The patterns of daily GPP and NPP through time approximated logistic curves under both CO 2 treatments. Regression analysis indicated that both the rate of increase (the parameter ‘ r ’) and the maximum value (the parameter ‘ k ’) of daily GPP and NPP under the elevated CO 2 treatment were significantly higher than under the ambient CO 2 treatment. The percentage increase in daily GPP due to elevated CO 2 varied systematically through time according to the logistic equations used for the two treatments. The GPP increase due to elevated CO 2 ranged from approximately 10% initially to 73% at the peak, while declining to about 33%, as predicted by the ratio of the two maximum values. Different values of percentage increase in GPP and NPP were obtained at different sampling times. This result demonstrated that one‐time measurements of percentage increases due to elevated CO 2 could be misleading, thereby making interpretation difficult. Although rhizosphere respiration was substantially enhanced by elevated CO 2 , no effect of elevated CO 2 on R:P (respiration:photosynthesis) was found, suggesting an invariant NPP:GPP ratio during the entire experiment. Further validation of the notion of an invariant NPP:GPP ratio may significantly simplify the process of quantifying terrestrial carbon sequestration by directly relating total photosynthesis to net primary production.

Investigating Climate Change Impacts and Thresholds: An Application of the CLIMPACTS Integrated Assessment Model for New Zealand Agriculture - G. J. Kenny; R. A. Warrick; B. D. Campbell; G. C. Sims; M. Camilleri; P. D. Jamieson; N. D. Mitchell; H. G. McPherson; M. J. Salinger (Climatic Change, 2000)

The physiological response of Atlantic salmon, Salmo salar L . , to a single experimental challenge with sea lice, Lepeophtheirus salmonis - J M Bowers; A Mustafa; D J Speare; G A Conboy; M Brimacombe; D E Sims; J F Burka (Journal of Fish Diseases, 2000)
The sea louse, Lepeophtheirus salmonis , is an ectoparasitic copepod of Atlantic salmon, Salmo salar L., capable of causing severe damage. This study was conducted to examine the physiological response of salmon to the stress of sea lice infestation. Smoltified salmon were acclimatized in 30‰ saltwater and exposed to high levels of lice infestation. The number of copepods per fish ranged from 15 to 285, with a mean of 106. The infested salmon were sampled six times over the 29‐d experimental duration and examined for alterations in the primary and secondary stress indicators, including plasma concentrations of cortisol, glucose, electrolytes, thyroid hormones T3 and T4, as well as the haematocrit level. The results were examined for correlations between the stress indicators, the number of copepods per fish and the life stage of the copepods. The presence of L. salmonis elevated stress indicators in relation to the specific sea lice stage. By day 21, both cortisol (mean 63.1 nmol L−1 controls: 179.8 nmol L−1 for parasitized) and glucose (mean 3.545 mmol L−1 controls: 4.567 mmol L−1 for parasitized) levels were significantly increased due to the presence of the lice. This was believed to be a direct result of the sea lice development into the larger life stages, thus increasing the level of host damage.

Carbon budgeting in plant–soil mesocosms under elevated CO 2 : locally missing carbon? - Weixin Cheng; Daniel A. Sims; Yiqi Luo; Dale W. Johnson; J. Timothy Ball; James S. Coleman (Global Change Biology, 2000)
Summary Studies have suggested that more carbon is fixed due to a large increase in photosynthesis in plant–soil systems exposed to elevated CO 2 than could subsequently be found in plant biomass and soils –‐ the locally missing carbon phenomenon. To further understand this phenomenon, an experiment was carried out using EcoCELLs which are open‐flow, mass‐balance systems at the mesocosm scale. Naturally occurring 13 C tracers were also used to separately measure plant‐derived carbon and soil‐derived carbon. The experiment included two EcoCELLs, one under ambient atmospheric CO 2 and the other under elevated CO 2 (ambient plus 350 μL L − 1 ). By matching carbon fluxes with carbon pools, the issue of locally missing carbon was investigated. Flux‐based net primary production ( NPP f ) was similar to pool‐based primary production ( NPP p ) under ambient CO 2 , and the discrepancy between the two carbon budgets (12 g C m − 2 , or 4% of NPP f ) was less than measurement errors. Therefore, virtually all carbon entering the system under ambient CO 2 was accounted for at the end of the experiment. Under elevated CO 2 , however, the amount of NPP f was much higher than NPP p , resulting in missing carbon of approximately 80 g C m − 2 or 19% of NPP f which was much higher than measurement errors. This was additional to the 96% increase in rhizosphere respiration and the 50% increase in root growth, two important components of locally missing carbon. The mystery of locally missing carbon under elevated CO 2 remains to be further investigated. Volatile organic carbon, carbon loss due to root washing, and measurement errors are discussed as some of the potential contributing factors.

Transplantation of sciatic nerve segments into normal and glia-depleted spinal cords - T. J. Sims; M. Barbaros Durgun; Shirley A. Gilmore (Experimental Brain Research, 1999)

Small (SK Ca ) Ca 2+ -activated K + channels in cultured rat hippocampal pyramidal neurones - A. A. Selyanko; J. A. Sim; D. A. Brown (Pflügers Archiv - European Journal of Physiology, 1998)

Mitochondrial DNA of the coral sarcophyton glaucum contains a gene for a homologue of bacterial muts: A possible case of gene transfer from the nucleus to the mitochondrion - Geneviàve Pont-Kingdon; Norichika A. Okada; Jane L. Macfarlane; C. Timothy Beagley; Cristi D. Watkins-Sims; Thomas Cavalier-Smith; G. Desmond Clark-Walker; David R. Wolstenholme (Journal of Molecular Evolution, 1998)

Nonlinearity of photosynthetic responses to growth in rising atmospheric CO 2 : an experimental and modelling study - YiqI. Luo; Daniel A. Sims; Kevin L. Griffin (Global Change Biology, 1998)
Nonlinear responses of photosynthesis to the CO 2 concentration at which plants were grown (C g ) have been often reported in the literature. This study was designed to develop mechanistic understanding of the nonlinear responses with both experimental and modelling approaches. Soybean (Glycine max) was grown in five levels of C g (280, 350, 525, 700, 1000 ppm) with either a high or low rate of nitrogen fertilization. When the rate of nitrogen fertilization was high, the photosynthetic rate measured at C g was highest in plants from the 700 ppm CO 2 treatment. When the rate of nitrogen fertilization was low, little variation was observed in the photosynthetic rates of plants from the different treatments measured at their respective C g . Measurements of CO 2 ‐induced changes in mass‐based leaf nitrogen concentration (n m , an index of changes in biochemical processes) and leaf mass per unit area (h, an index of morphological properties) were used in a model and indicate that the nonlinearity of photosynthetic responses to C g is largely determined by relative changes in photosynthetic sensitivity, biochemical downregulation, and morphological upregulation. In order to further understand the nonlinear responses, we compiled data from the literature on CO 2 ‐induced changes in n m and h. These compiled data indicate that h generally increases and n m usually decreases with increasing C g , but that the trajectories and magnitudes of the changes in h and n m vary with species and growth environments. Integration of these variables (n m and h) into a biochemically based model of photosynthesis enabled us to predict diverse responses of photosynthesis to C g . Thus a general mechanism is suggested for the highly variable, nonlinear responses of photosynthesis to C g reported in the literature.

Regulation of desmosomal cell adhesion in human tumour cells by polyunsaturated fatty acids - Wen G. Jiang; Sim K. Singhrao; Stephen Hiscox; Maurice B. Hallett; Richard P. Bryce; David F. Horrobin; Malcolm C. A. Puntis; Robert E. Mansel (Clinical & Experimental Metastasis, 1997)

Basking shark occurrence off south‐west England in relation to zooplankton abundance - D. W. Sims; A. M. Fox; D. A. Merrett (Journal of Fish Biology, 1997)
Basking sharks Cetorhinus maximus >3 m total length arrived off Plymouth, U.K. directly after the increase in zooplankton density in May, while young‐of‐the‐year basking sharks ( −3 ). No basking sharks were seen after July when the zooplankton density was least.

Uptake and transport of phosphorus by Agrostis capillaris seedlings from rapidly hydrolysed organic sources extracted from32 P-labelled bacterial cultures - A.E.S. Macklon; S.J. Grayston; C.A. Shand; A. Sim; S. Sellars; B.G. Ord (Plant and Soil, 1997)

Linear and nonlinear stiffness and friction in biological rhythmic movements - P. J. Beek; R. C. Schmidt; A. W. Morris; M. -Y. Sim; M. T. Turvey (Biological Cybernetics, 1995)

A note on the kinetics of uptake of d-glucose by the food yeast, Candida utilis - James A. Barnett; Anthony P. Sims (Archives of Microbiology, 1976)

Some physiological observations on the uptake of d-glucose and 2-deoxy-d-glucose by starving and exponentially-growing yeasts - James A. Barnett; Anthony P. Sims (Archives of Microbiology, 1976)